When introduced equals invasive: normative use of “invasive” with ascidians - Pereyra, Patricio Javier (2018)
This study aimed to understand the use of “invasive species” as a normative concept and discuss its implications in conservation science, using introduced ascidians worldwide as model species. A specific search in Web of Science was performed and articles suitable for analysis were selected. Each article was classified according to the type of environment, species under study, type of effects and spread that ascidians are linked to. Most of the 184 articles analysed did not consider dispersal or effects as study subject (82 and 71%, respectively). Most research was conducted in laboratory conditions (41%) or human-made environments (32%) or indicating few escapes to natural environments. Almost half of the articles (47%) were made with the six more conspicuous introduced ascidians and this raised to 70% while considering articles that worked with two or more (pooled) species. The normative use of “invasive” is widely used regarding introduced ascidians. Spread and effects, necessary conditions to consider a species as invasive, are notoriously understudied. Most research was not conducted in natural environments and over a few species, weakening the perception of introduced ascidians as a conservation problem. To discuss the extent of the normative use of invasion science is important to distinguish two phenomena: are some species intrinsically problematic for conservation (i.e. invasive) or is the movement of non-native species (i.e. biological invasion) the conservation problem? By using invasive as a normative concept, we risk ending with a weakened concept potentially hindering the progress of invasion science.